TOMS observations of total ozone in the 1986 Antarctic spring - Krueger, A. J.; Schoeberl, M. R.; Stolarski, R. S. (1987)
Total ozone measurements by the Total Ozone Mapping Spectrometer (TOMS) aboard the Nimbus 7 satellite show the reappearance in 1986 of the extreme springtime Antarctic ozone minimum during September and October.The minimum total ozone amounts descended to 156 Dobson Units; the minimum October average of 185 DU was 27 DU higher than the corresponding average in 1985 and 5 DU less than the 1984 average. This behavior indicates a pause in the downward trend of recent years.